Poverty and protected areas: An evaluation of a marine integrated conservation and development project in Indonesia - Gurney, Georgina G.; Cinner, Joshua; Ban, Natalie C.; Pressey, Robert L.; Pollnac, Richard; Campbell, Stuart J.; Tasidjawa, Sonny; Setiawan, Fakhrizal (Global environmental change, 2014)
•We evaluated the social impacts of integrated development and protected area projects.•We used pre-, mid- and post-implementation data for sites with and without projects.•Projects appeared to contribute to alleviating three key domains of poverty.•Positive impacts spanned all domains but magnitude and timescale of impacts differed.•Reductions in poverty did not continue to accrue after the implementation period. Protected areas are currently the primary strategy employed worldwide to maintain ecosystem services and mitigate biodiversity loss. Despite the prevalence and planned expansion of protected areas, the impact of this conservation tool on human communities remains hotly contested in conservation policy. The social impacts of protected areas are poorly understood largely because previous evaluations have tended to focus on one or very few outcomes, and few have had the requisite data to assess causal effects (i.e. longitudinal data for protected and control sites). Here, we evaluated the short-, medium- and long-term impacts of marine protected areas (MPAs) that were specifically designed to achieve the dual goals of conservation and poverty alleviation (hereafter “integrated MPAs”), on three key domains of poverty (security, opportunity and empowerment) in eight villages in North Sulawesi, Indonesia. Using social data for villages with and without integrated MPAs from pre-, mid- and post-the five-year implementation period of the integrated MPAs, we found that the integrated MPAs appeared to contribute to poverty alleviation. Positive impacts spanned all three poverty domains, but within each domain the magnitude of the effects and timescales over which they manifested were mixed. Importantly, positive impacts appeared to occur mostly during the implementation period, after which integrated MPA activities all but ceased and reductions in poverty did not continue to accrue. This finding questions the efficiency of the short-term approach taken in many international donor-assisted protected area projects that integrate development and conservation, which are often designed with the expectation that project activities will be sustained and related benefits will continue to accumulate after external support is terminated.